THE EFFECTS OF TRANSFER PRICING, THIN CAPITALIZATION, FIRM SIZE, AND TAX HAVEN COUNTRY UTILIZATION ON TAX AGGRESSIVENESS - Ruknan, Ruknan; Khair, Oki Iqbal; Diraga, Muhammad Givary (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research aims to examine the effects of transfer pricing, thin capitalization, firm size, and tax haven country utilization on tax aggressiveness. This study uses manufacturing sector companies listed on Indonesia Stock Exchange (IDX) during 2017 – 2021 period. The total of samples used were 14 manufacturing sector companies for 5 years. This study used multiple linear regression analysis with the assistance of SPSS 25. The results of this research indicated that transfer pricing and thin capitalization have no effect on tax aggressiveness. While, firm size has a positive and significant effect on tax aggressiveness. Also, tax haven country utilization has negative and significant effect on tax aggressiveness This research have an implication for related parties, especially the Directorate General of Taxes of the Republic of Indonesia and taxpayers in minimizing tax aggressiveness Keywords : Aggressiveness, Transfer Pricing, Capitalization, Firm, Haven, Tax